KARDIOCHIRURGIA DOROSŁYCHIs C-reactive protein level before cardiac operations for the most common indications helpful in risk prediction of in-hospital postoperative complications? - Bitner, Mirosław; Jander, Sławomir; Walczak, Andrzej; Bartczak, Karol; Misztal, Małgorzata; Jegier, Bogdan; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: Studies on this topic use different CRP cut-off values and their results are divergent. Aim: To answer the question: can preoperative CRP>5 mg/L predict either atrial fibrillation, or other complications in patients who underwent heart operation? Material and Methods: 85 patients underwent operations: 59 for CAD (51 on, 8 off-pump), and 26 for valve diseases (aged from 21 to 78 years, 61 male, 24 female). 39 (45.8%) had increased CRP level (range: 6.7-131.2; 24.97±24.71 mg/L on average), and 46 (54.2%) had normal (range: 0-4.5; 1.78±1.11 mg/L on average; p<0.001). Age, gender, preoperative EF and CRP, maximal CKMB, and WBC with neutrophil percentage at discharge were compared in two pairs of contrary groups: with/without complications, and with paroxysmal AF/sinus rhythm. Receiver operating characteristic (ROC) curves were drawn for both pairs of groups. Results: Patients with complications were significantly older, and had significantly higher CKMB, whereas other parameters in these groups, as in all AF/sinus rhythm ones, did not differ. The ROC curves confirmed that preoperative CRP level does not discriminate between patients and there is no sense in looking for a cut-off point. Conclusions: Increased preoperative CRP value cannot be a predictor of complicated early outcome after heart surgery. Better cut-off CRP predictive value cannot be found. Complications, except for AF, were depended on higher age, and myocardial injury represented by increased postoperative CKMB level. Despite a lack of statistical evidence, a delay of elective operations should possibly be considered in patients with very high CRP level.